Control of Healthcare-Associated Carbapenem-Resistant Acinetobacter baumannii by Enhancement of Infection Control Measures - Shuk-Ching Wong; Pui-Hing Chau; Simon Yung-Chun So; Germaine Kit-Ming Lam; Veronica Wing-Man Chan; Lithia Lai-Ha Yuen; Christine Ho-Yan Au Yeung; Jonathan Hon-Kwan Chen; Pak-Leung Ho; Kwok-Yung Yuen; Vincent Chi-Chung Cheng (MDPI AG, 2022)
Antimicrobial stewardship and infection control measures are equally important in the control of antimicrobial-resistant organisms. We conducted a retrospective analysis of the incidence rate of hospital-onset carbapenem-resistant Acinetobacter baumannii (CRAB) infection (per 1000 patient days) in the Queen Mary Hospital, a 1700-bed, university-affiliated teaching hospital, from period 1 (1 January 2007 to 31 December 2013) to period 2 (1 January 2014 to 31 December 2019), where enhanced infection control measures, including directly observed hand hygiene before meal and medication rounds to conscious patients, and the priority use of single room isolation, were implemented during period 2. This study aimed to investigate the association between enhanced infection control measures and changes in the trend in the incidence rate of hospital-onset CRAB infection. Antimicrobial consumption (defined daily dose per 1000 patient days) was monitored. Interrupted time series, in particular segmented Poisson regression, was used. The hospital-onset CRAB infection increased by 21.3% per year [relative risk (RR): 1.213, 95% confidence interval (CI): 1.162-1.266, p < 0.001], whereas the consumption of the extended spectrum betalactam-betalactamase inhibitor (BLBI) combination and cephalosporins increased by 11.2% per year (RR: 1.112, 95% CI: 1.102-1.122, p < 0.001) and 4.2% per year (RR: 1.042, 95% CI: 1.028-1.056, p < 0.001), respectively, in period 1. With enhanced infection control measures, the hospital-onset CRAB infection decreased by 9.8% per year (RR: 0.902, 95% CI: 0.854-0.953, p < 0.001), whereas the consumption of the extended spectrum BLBI combination and cephalosporins increased by 3.8% per year (RR: 1.038, 95% CI: 1.033-1.044, p < 0.001) and 7.6% per year (RR: 1.076, 95% CI: 1.056-1.097, p < 0.001), respectively, in period 2. The consumption of carbapenems increased by 8.4% per year (RR: 1.84, 95% CI: 1.073-1.094, p < 0.001) in both period 1 and period 2. The control of healthcare-associated CRAB could be achieved by infection control measures with an emphasis on directly observed hand hygiene, despite an increasing trend of antimicrobial consumption.